Peran Kepemimpinan Kyai pada Organisasi Lembaga Pesantren di Ponpes Asyrofuddin Conggeang Kab. Sumedang - Ramdhani, Deden; Andriyana, Muhammad (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2023)
This research is motivated by the role of the kiai figure who is a central figure in Islamic boarding schools where the kyai has its own leadership characteristics compared to other educational figures. In practice, the kyai assigns a special organization whose job is to take care of all matters relating to the santri. The pesantren organization will run optimally if the Kyai directly monitors and supervises the activities and work programs in the organization. The role of the kyai in leading the pesantren organization greatly influences the performance carried out by its members. The purpose of this study was to determine the leadership strategy and leadership role of the kyai in the pesantren organization at the Asyrofuddin Conggeang Sumedang Islamic boarding school. The results of this study indicate that the kyai's leadership strategy in fostering the Islamic boarding school organization in Asyrofuddin Islamic boarding school includes dividing the three executive boards of the Islamic boarding school, selecting members of the organization and the executive board, fostering the Islamic boarding school organization.